Partial volume effect correction technique using adaptive region growing template for SPECT quantification - A/P Velo, Parimalah (2019)
Partial volume effect (PVE) occurs due to limited spatial resolution of the gamma camera which degrades the quantitative accuracy in SPECT imaging. The aim of this study was to develop and evaluate the template based adaptive region growing method to correct for PVE in SPECT images of small target objects with background activities. Using a validated Geant4 Application of Tomography Emission (GATE) simulation model, SPECT images of rectangular phantom containing target objects of various sizes ranged from 1.44 ml to 10.1 ml surrounded by radioactivity with target to background activity concentration (T/B) ratio of 1.25, 2.5 and 5.0 were simulated. PVE correction was applied on each simulated SPECT data. Then the SPECT slices were reconstructed using filtered backprojection method. Image contrast, total counts, volume of target object and activity concentration were quantified using SPECT projections with and without PVE correction. The results were then compared. For all T/B, the edges of hot region of interest (ROI) were enhanced with PVE correction. Improvement in contrast of target objects were observed for SPECT images with PVE correction. For SPECT slices with high background activity (T/B=1.25), the counts in target objects increased up to 40% after PVE correction for object size larger than 6.3 ml. For object size less than 6.3 ml, the counts in target objects increased up to 55% after PVE correction. For SPECT images with low background activity, the counts in the target objects increased more than 50% after PVE correction for all target objects. The agreement between simulated volume and estimated volume of target objects with PVE correction (R2=0.3715) was better compared to without PVE correction (R2=0.1077). Similarly, the agreement between simulated radioactivity concentration and estimated radioactivity concentration was better with PVE correction (R2=0.9512) compared to without PVE correction (R2=0.9444). In conclusion, the developed PVE correction technique improved the accuracy of SPECT quantification.